2011
DOI: 10.1530/eje-11-0067
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and infant growth and the risk of obesity during early childhood: the Generation R Study

Abstract: Objective: To examine whether infant growth rates are influenced by fetal growth characteristics and are associated with the risks of overweight and obesity in early childhood. Design: This study was embedded in the Generation R Study, a population-based prospective cohort study from fetal life onward. Methods: Fetal growth characteristics (femur length (FL) and estimated fetal weight (EFW)) were assessed in the second and third trimesters and at birth (length and weight). Infant peak weight velocity (PWV), pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 32 publications
6
70
0
1
Order By: Relevance
“…These measures took place at the ages of 1,2,3,4,6,11,14,18,24,36 and 48 months, based on the national health care program in the Netherlands. Peak weight velocity and peak height velocity in infancy were derived using the Reed1 model for boys and girls separately, as described in detail previously.…”
Section: Infant Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…These measures took place at the ages of 1,2,3,4,6,11,14,18,24,36 and 48 months, based on the national health care program in the Netherlands. Peak weight velocity and peak height velocity in infancy were derived using the Reed1 model for boys and girls separately, as described in detail previously.…”
Section: Infant Growthmentioning
confidence: 99%
“…Peak weight velocity and peak height velocity in infancy were derived using the Reed1 model for boys and girls separately, as described in detail previously. 13,14,19,20 The Reed1 model is a four-parameter model that is fitted by gender on all weight and height measurements in children aged 0-3 years, including birth weight and length. We assumed both a fixed and a random component for all four parameters.…”
Section: Infant Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies suggested that infant growth rates are the strongest risk factor for overweight (8,11,12). Infant and fetal growth rates are highly inversely correlated (15). Decelerated fetal growth in the second or third trimester and accelerated fetal growth in the third trimester have been associated with a higher fat mass percentage at 6 mo of age (16).…”
mentioning
confidence: 99%